Sosialisasi Peranan Digital Marketing Bagi Pelaku UMKM Di Desa Bandar Khalipah - Revita Sari; Abdul Riduan (CV. Multi Kreasi Media, 2025)
In community service activities in Bandar Khalipah Village, Percut Sei Tuan, North Sumatra, it was found that MSME actors still use traditional promotional methods, such as brochures and verbal information delivery. This deficiency limits the movement of MSMEs to the local environment. In the digital era, social media is an effective tool for reaching a wider target market. Social media allows for fast and easy-to-share information dissemination, and provides feedback that can be immediately accessed and analyzed. Therefore, the author decided to conduct promotional socialization activities through digital marketing to develop the MSME sales market in Bandar Khalipah Village so that the public knows how important promotion and sales are on social media.